Analysis of freight mode choice decisions of shippers and forwarders: pre-liberalisation survey. (20th September 2019) - Zeybek, Hulya
Liberalisation of rail markets has been in progress in the EU since the beginning of 2007. This allows any licensed EU incumbent or non-incumbent railway company with the necessary safety certification to apply for capacity and offer freight services by rail throughout the EU. The experiences of the liberalised rail markets demonstrate that the majority of the new rail freight services providing companies have drawn customers from incumbents and very few companies have been successful in attracting new ones. Thus, unleashing competition by opening the market requires the incumbents to understand customers' mode and carrier choice behaviour as a first step, if they are to avoid dramatic and rapid losses of market share. This study provides an assessment of the influences on the transport mode choice of shippers and forwarders highlighting the important factors driving freight mode choice before the rail market liberalisation. The analysis is based on the findings of the survey conducted by interviewing shippers and forwarders. The results of the research revealed that cost is the main factor in determining the modal choice of both shippers and forwarders demonstrating that they are price sensitive in transport service procurement.